2011
DOI: 10.1248/bpb.34.1418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-Fluorouracil Treatment on SN-38 Absorption from Intestine in Rats

Abstract: The pyrimidine analog 5-fluorouracil (5-FU) is an essential drug for metastatic carcinomas of gastrointestinal, breast, ovary, head and neck tumors.1-4) 5-FU-based combination chemotherapies have been applied for the treatment of tumors 2,5,6) ; for example, the FOLFIRI (5-FU, leucovorin and irinotecan) regimen has been a standard chemotherapy for colorectal cancer. 7) Randomized trials have demonstrated improvements in progression-free and overall survival when irinotecan (CPT-11) has been added to fluorourac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Also, Guichard et al reported improved anti-tumor efficacy by administrating irinotecan before 5-FU, but also noted increased toxicity [45]. Moreover, other studies have also suggested an inverse relationship, i.e., pre-treatment with 5-FU mediated downregulation of P-glycoprotein and breast cancer resistance protein, correlated with enhanced SN absorption and efficacy [46]. This is supported by clinical observations but was simultaneously correlated with reduced tolerability [47].…”
Section: Discussionmentioning
confidence: 83%
“…Also, Guichard et al reported improved anti-tumor efficacy by administrating irinotecan before 5-FU, but also noted increased toxicity [45]. Moreover, other studies have also suggested an inverse relationship, i.e., pre-treatment with 5-FU mediated downregulation of P-glycoprotein and breast cancer resistance protein, correlated with enhanced SN absorption and efficacy [46]. This is supported by clinical observations but was simultaneously correlated with reduced tolerability [47].…”
Section: Discussionmentioning
confidence: 83%
“…Protein sampling and the western blot analysis were performed as described previously ( 15 ). Whole cell homogenates (β-actin, 5 μ g; other proteins, 20 μ g) were separated using 10% SDS polyacrylamide gels and proteins were then transferred to a nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were incubated with either the AC-74 (10,000-fold dilution), 5C10 (1,000-fold dilution), 104A282 (1,000-fold dilution), 1C1 (500-fold dilution) or NB500-210SS (2,000-fold dilution) monoclonal antibody and with the rabbit polyclonal antibody (1,000-fold dilution) in the blocking solution. The detection method has been described in detail previously ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…INTRODUCTION 5-Fluorouracil (5-FU) is considered one of the most effective agents against metastatic carcinomas of the gastrointestinal tract, mammary gland, ovary, and head and neck ( Shibayama et al, 2011 ;Lamberti et al, 2012). It is an antimetabolite that acts during the S phase of the cell cycle and is activated by thymidine phosphorylase into fluorodeoxyuridylate 5 ( -fluoro 2 , deoxyuridine, 5 -monophosphate -5 FdUMP) that inhibits thymidylate synthase, thus preventing DNA synthesis, that leads to imbalanced cell growth and ultimately cell death (Abd-Ellah, 2012).…”
Section: ‫ـــــــــــــــــــــــــــــــ‬ ‫ـــــــــــ‬ ‫ـ‬ ‫ـــــــmentioning
confidence: 99%